CT in progressive supranuclear palsy. - Ambrosetto, P (American Journal of Neuroradiology, 1987)
To determine the usefulness of CT in progressive supranuclear palsy (PSP), the CT scans of 87 patients with extrapyramidal disorders and/or dementia were reviewed. Of these, eight patients whose CT scans showed the findings characteristic of PSP were selected for study. These findings consisted of atrophy of the midbrain and quadrigeminal plate, with prominent interpeduncular, crural, ambient, and quadrigeminal plate cisterns, and dilatation of the aqueduct and posterior third ventricle. All eight patients were found to have PSP while none of the other patients had a clinical diagnosis of PSP. The importance of CT in the diagnosis of PSP, especially in the early phases of the disease, is emphasized.